Prospective Regulation of Private Sector Legal Compliance Audits Through the Draft National Legal Guidance Law as A Manifestation of Good Corporate Governance - Kusworo, Daffa Ladro (Universitas Muhammadiyah Malang, 2024)
Various private-sector legal issues show how the quality of legal compliance is lacking. Legal and business entities have not considered decision-making in business transactions or other actions that risk-reducing investor interest. The massiveness of legal audit problems is an urgency to identify legal deviations from the start to measure legal compliance to avoid criminal, civil, and administrative sanctions. However, reviewing the current implementation of legal audits is limited to asset valuation and financial statements, and even then, it does not require private institutions to carry out audits periodically, so they are carried out by certain companies only. This research uses a normative method that refers to laws and regulations accompanied by literature studies in the form of books, journals, and other literature to find prescriptive ideal ideas. The results show that the implications of legal compliance audits stem from a legal vacuum over the audit mechanism, standardization of honorarium, and legality of legal auditors. The National Law Development Agency (BPHN) must collaborate to formulate a private sector legal compliance audit in the Draft Law on National Law Development to realize Good Corporate Governance (GCG). The author recommends an ideal legal compliance audit model like the Government Accountability Office (GAO) in the United States.